Entropy generation for natural convection in ?-shaped enclosures - Dagtekin, Ihsan; Öztop, Hakan Fehmi; Bahloul, Ali (Pergamon-Elsevier Science Ltd, 2007)
This study deals with the prediction of entropy generation (EG) for natural convection in a F-shaped enclosure. Heat removal is achieved from cooler vertical sides while the horizontal walls are insulated perfectly. The results are reported with streamlines, isotherms, mean Nusselt numbers, EG due to heat transfer and fluid friction for Ra number ranging from 10(3) to 10(6), irreversibility distribution ratio phi, ranging from 10(-5) to 10(-3), different step height (h) and step width (w) values. It is observed that at a fixed Ra number, with an increase in aspect ratio (AR=h/w) mean Nusselt number values increase. For Ra numbers ranging from 10(3) to 10(4), the total EG is mostly due to heat transfer because of relatively low velocities, but for Ra > 10(4) the contribution to due to fluid friction becomes effective even has comparable values from Ra = 10(5) to Ra = 10(6). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: natural convection; entropy generation; Gamma-shaped enclosure